Contesting the Non-Muslim Existence In a Democratic State: A Trajectory to Hack Majority-Minority Relations In Indonesia - Ubaidillah, Muchamad Faiz (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2024)
The outbreak of inter-religious conflict today is mostly caused by unequal majority-minority relations, especially in the context of a democratic state—Indonesia. Therefore, it is necessary to reconcile and integrate the Islamic paradigm with the democratic system, especially in a country dominated by one religion. In this article, the author analyzes the social friction between the majority and minority with an intertextuality approach between classical Sunni literature and the development of modern democratic discourse. The author finds that the tradition of Sunni classical fiqh literature was born from scholars who used to live under the auspices of religious states that still considered non-Muslims as second-class citizens. In addition, this article reviews the concepts of state religion and state democracy and the social conflicts that may occur in them. Finally, the author tries to provide an alternative way to integrate the Islamic paradigm and the concept of citizenship and secularization efforts in the form of separation between religious identity and identity as a citizen for better democratic state conduct.